CLONING OF BRAZZEIN GENE (SWEET PROTEIN) INTO PBI121 VECTOR THROUGH PROKARYOTIC EXPRESSION SYSTEM - B. Saleh; N. Huma; A. Azhar; S. Galani (Journal of Animal and Plant Sciences, 2023)
Brazzein- a low-calorie natural sweetener is an effective substitute for deleterious effects of sucrose. Uptill now, limited production of recombinant brazzein protein using heterologous expression system along with solubility and low yield challenges are reported. Foreseeing the potential of brazzein gene in therapeutics, molecular strategies are required to optimize production of recombinant brazzein using different prokaryotic and eukaryotic expression systems. Therefore, in this study brazzein gene synthesized from Bio Basic Inc. (BBI) which was provided in pUC57 cloning vector. The gene was retrieved from cloning vector by performing PCR andcloned in plant expression vector pBI121 with CaMV35S promoter region. Heat shock or calcium chloride method was optimized for transformation into E. coli (DH5-alpha) with recombinant vector pBI121. Kanamycin resistence selection, colony PCR and transformation efficiency analysis were performed to analyze the successful cloning procedure. Transformed cultures having cloned brazzein gene in pBI121 vector with CaMV35S promoter could be used to transform different plants such as, sorghum, sugarcane and turnip for sweet taste enhancement in future and may provide plateform for commercial scale production of therapeutic proteins using crop plants as bioreactor.
Keywords: Brazzein; pBI121 vector; Recombinant technology; Transgenic plants